Characterizing Asian American medical students’ experiences with microaggression and the impact on their well-being - Lindy Zhang; Crystal An; Joanna Chen; B U.K. Li; Sunny Nakae; Joyce Pang (Medical Education Online)
Purpose This mixed-methods study quantified and characterized incidents of microaggressions experienced by Asian American medical students. The authors report on their impact and suggest improvements to create a more equitable and supportive learning environment.Method Quantitative and qualitative data were collected from 305 participants who self-identified as Asian American or Pacific Islander. An online, anonymous survey was sent to US medical students through the Asian Pacific American Medical Student Association (APAMSA). Questions explored incidence, characteristics of, and response to microaggressions. We conducted four focus groups to further characterize students’ experiences. Data were organized and coded, and thematic analysis was used to identify core themes.Results Racial microaggressions were prevalent among Asian American medical students. Nearly 70% (n = 213) of survey respondents reported experiencing at least one incident during their medical training to date. The most common perpetrators were patients (n = 151, 70.9%) and fellow medical students (n = 126, 59.2%), followed by professors (n = 90, 42.3%). The most prevalent themes included being perceived as a perpetual foreigner, the assumption of timidness, and ascription of the model minority myth. Students rarely reported the incident and usually did not respond immediately due to fear of retaliation, uncertainties about the experience or how to respond appropriately, and perception that they would bear the burden of advocacy alone. Experiences with microaggressions led to feelings of frustration and burnout and had a negative impact on mental health. Recommendations were made to improve the anonymous reporting systems in medical schools, and to increase diversity and inclusion in medical education and leadership.Conclusions Asian American medical students face high exposure to racial microaggressions during their medical education that adversely impact their mental health. Changes are needed in medical training to create a more equitable and inclusive learning environment.